The relationship between attitudes towards healthy nutrition and awareness levels of exercise addiction in male taekwondo athletes - Ersan Tolukan; Hasan Guler; Aydiner Birsin Yildiz; Guner Cicek; Ilimdar Yalcin; Alican Bayram; Nurullah Emir Ekinci (Journal of Men's Health)
Exercise has a vital role in the physical, mental, emotional and social health of individuals. However, excessive and uncontrolled exercise may have negative consequences instead of the expected benefits such as exercise addiction. Studies on exercise addiction in athletes are thus crucial. In this regard, the present study was aimed to examine the relationship between male taekwondo athletes’ attitudes towards healthy nutrition and their awareness levels of exercise addiction. Data for the study were collected in 2024 from 282 Turkish taekwondo athletes selected through convenience sampling. The average sports experience of study participants was 9.3 ± 5.7 years. The questionnaire for data collection had three parts: the personal information form, the Attitude Scale for Healthy Nutrition Awareness, and the Exercise Addiction Scale. A Pearson correlation coefficient was calculated to analyze the relationships between variables wherein the data showed normal distribution. A simple regression analysis was performed to examine the effects. An independent t-test was conducted to explore differences between the national and non-national athletes. Results demonstrated that the national athletes had higher exercise addiction scores. The study found significant and positive relationship between male taekwondo athletes’ attitudes towards healthy nutrition and their awareness levels of exercise addiction (p < 0.05). The attitudes towards healthy nutrition significantly predicted exercise addiction awareness (p < 0.05; r = 0.186). The increase in positive attitudes towards healthy nutrition may bring greater awareness of exercise addiction. Efforts should be made to improve athletes’ attitudes towards nutrition for preventing exercise addiction as a negative outcome. Further studies are recommended to enhance athletes’ knowledge and attitude towards nutrition.